Factors associated with student dropout in pharmacy regency and radiodiagnosis technologies - Pérez Basante, María Constanza; Rosero Montezuma, Doony Harvey (SATHIRI, 2021)
Objective: The article is the result of teacher research carried out in two technology programs, based on the need to make a diagnosis about the factors that are associated with school dropout, such as individual, social, economic and institutional. Methodology: A descriptive quantitative study was carried out with two groups of students who dropped out of the Pharmacy Regency Technology programs (40 subjects) and Radiodiagnosis and Radiotherapy technology from a Private University, in the city of San Juan de Pasto, using as instrument a questionnaire of 27 closed questions. Results: they show that due to economic and personal factors such as pregnancy they were the main causes of desertion for Regency of Pharmacy and lack of family support for the Radiodiagnosis and Radiotherapy program. Conclusions: the Institution must promote permanence strategies according to the interests of the students, the demotivation and low interest lie in that the institution did not have an approach to these shortcomings.